Association Between Body Posture and Incidence of Work-Related Musculoskeletal Disorders (MSDS) - Anum Anwar, Muhammadahmed Khan, Khadija Saeed, Syeda Aiman Batool, Iqra Ibrar, Shumaila Maqsood, Usama Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
The paper seeks to highlight the most important agronomical risk factor ‘Posture’ as the major contributors for the musculoskeletal disorders in handicraft sector. Methodology: The sample size calculated was 75. The questionnaire was comprised of multiple choice options. Questionnaire will include part Braggs Posture Chart and part Nordic Musculoskeletal Questionnaire-Extended. The data was collected by questionnaire form set on paper. The purpose of the study was delivered verbally among the participants and written consent was also taken. Results: Poor and fair posture was noticed in all regions. Trouble in neck, shoulder, wrist, and lower back in last year was 54.7%, 64%, 56% and 64%. Trouble in last week in neck, shoulder, wrist and lower back was 56%, 54.7%, 54.7% and 60%.Association between posture and musculoskeletal disorders was checked by chi square test which showed significant association as p-value. Conclusion: It is concluded by the results that there is a significant association between the posture and the musculoskeletal disorders in the handicraft sector. The association varies with the regions of body involved and the type of occupation.